Propulsion in the butterfly stroke - Mason, B. R.; Tong, Z.; Richards, R. J. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
This study examined the intra-stroke velocity and acceleration of the centre of gravity (CG) of elite bufferfly swimmers. The purpose of the research was to understand more about the propulsive nature of the stroke and identify if the velocity and acceleration profiles of the swimmers' hip would adequately reflect the corresponding CG profiles. An analysis of the results (n = 11) revealed that the hip parameters could not reliably be substituted for those of the swimmers' CG. The profiles of the swimmers' hips were found to fluctuate with greater magnitude and were out of phase with the velocity and acceleration profiles of the CG. The CG acceleration profiles illustrated that there were five distinct propulsive phases in the stroke. If hand entry was considered as the start of the stroke, the acceleration peaks occurred at the kick (1.9 m/s- 2), outsweep of arms (1.4 m/s- 2), insweep of arms (4.2 m/s- 2), concurrent kick with upsweep of arms (2.3 m/s- 2 ) and finally catching the wave (O.Q m s- 2). The last propulsive phase did not correspond to any particular movement of the arms or legs and on observation was associated with the swimmers' actions of riding the wave produced by the swimming action itself.